Linking morphology to thermal conductivity in PEDOT: an atomistic investigation. (14th November 2017) - Genovese, Claudio; Antidormi, Aleandro; Dettori, Riccardo; Caddeo, Claudia; Mattoni, Alessandro; Colombo, Luciano; Melis, Claudio
Abstract: Among different conducting polymers, poly(3, 4-ethylenedioxythiophene) (PEDOT) and its doped mixtures are promising candidates for thermoelectric applications due to their intrinsically low thermal conductivity. An accurate estimate of the overall thermoelectric figure of merit requires a sharp thermal conductivity measurement. However, even for pristine PEDOT, the estimated thermal conductivity values show high fluctuations depending on the synthesis procedure employed, suggesting that morphology can be one of the key factors affecting PEDOT thermal conductivity. In this work, we elucidate this issue by demonstrating how morphology ultimately governs thermal transport properties. By means of the approach to equilibrium molecular dynamics method, we estimate thermal conductivity of PEDOT systems with a controlled degree of crystallinity. We show that by going from pure crystalline to nearly amorphous PEDOT samples, a thermal conductivity reduction of more than two orders of magnitude is obtained. Moreover a strong thermal conductivity increase with the PEDOT chain length is observed independently of the degree of crystallinity.